2020
DOI: 10.3892/ol.2020.11934
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan induces ROS‑dependent cell death and autophagy in A375 melanoma cells

Abstract: Melanoma is a common type of cutaneous tumor, but current drug treatments do not satisfy clinical practice requirements. At present, mitochondrial uncoupling is an effective antitumor treatment. Triclosan, a common antimicrobial, also acts as a mitochondrial uncoupler. The aims of the present study were to investigate the effects of triclosan on melanoma cells and the underlying mechanisms. Mitochondrial membrane potential (MMP), mitochondrial morphology, mitochondrial reactive oxygen species (mito-ROS), intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In agreement with the increased pAMPK level, acetylCoA carboxylase enzyme (ACC), which is a known target of AMPK activity, has been found phosphorylated as well (pACC, Figure 4 ). AMPK is an activator of mitophagy/autophagy in tumor cells, including melanoma [ 52 ]. Therefore, the expression level of microtubule-associated proteins 1A/1B light chain 3B (LC3B), a known marker of autophagy, was investigated by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the increased pAMPK level, acetylCoA carboxylase enzyme (ACC), which is a known target of AMPK activity, has been found phosphorylated as well (pACC, Figure 4 ). AMPK is an activator of mitophagy/autophagy in tumor cells, including melanoma [ 52 ]. Therefore, the expression level of microtubule-associated proteins 1A/1B light chain 3B (LC3B), a known marker of autophagy, was investigated by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…This finding aligns with previous studies in the literature, which have shown that the incorporation of antibacterial agents, such as Tri, can have an impact on cell viability. 55 57 The cytotoxicity of Tri has been reported with respect to various cell types, and its effects can be dose-dependent. 58 It is worth noting that in this study the cell viability remains at 70% and above, up to the 20 TPP sample.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in A375 and BLM cell lines, both autophagy and apoptosis were induced by the proteasome inhibitor bortezomib through the involvement, at least in part, of the ROS-mitochondrial dysregulation-associated pathways [ 91 ]. Mitochondrial dysfunction was also induced by treatment with the antimicrobial triclosan in A375 cells [ 92 ]. Triclosan caused cytotoxicity and cell death acting on ROS signalling and promoting autophagy.…”
Section: Melanoma Cell Death and Survival: Simultaneous Regulation Of Oxidative Stress System And Autophagy Machinerymentioning
confidence: 99%